The Impact of Social Capital on the Labour Market Outcome: The Case of Tamale Metropolis - Shaibu, Hakeem (2012)
A Thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Commonwealth Executive Masters of Business Administration